Korespondensi dan Presentasi Bisnis Serta Penanganan Keluhan Pelanggan - Sri Wahyuni; Muhammad Farhan Harahap; Dedy Rahman Siregar (Universitas Muhammadiyah Surabaya, 2023)
Abstrac Business correspondence has a very important role to convey information, ideas, and requests that support activities. The exchange of information and ideas is the key to the smooth running of business activities. Correspondence also functions as a filing system as well as an important source of information to support their duties as intermediaries between exporters and importers. This writing method is obtained from scientific journals and also reliable books which contain some material about correspondence and business presentations and handling customer complaints, this research uses the method of literature and analytical studies. The purpose of this journal is to understand more broadly about